A criança e a transição da educação infantil para o ensino fundamental - SILVA, Gilviane Carla Silva da (2024)
The article corresponds to the final paper of the Pedagogy degree course, entitled "The child and the transition from nursery school to elementary school". The study's objectives are to analyze the behavioral changes that occur during the transition process from kindergarten to elementary school and to analyze the relevant challenges in the transition process from kindergarten to elementary school. The theoretical framework is based on authors who study childhood, early childhood education and nine-year primary education, such as: Sônia Kramer (2006/2007), Nascimento (2007), Peretti (2016), Correa (2012), Melo (2020), among others. As a methodological research option, content analysis was used, through a bibliographic review with a qualitative approach. Having analyzed and discussed the challenges posed by the new organization of primary education, within the limits of this work, we have highlighted the importance of educational institutions rethinking strategies for the inclusion of six-year-olds, considering that they are linked to the teaching they experienced in the early childhood education stage, as well as the need for adequate training for teachers who will work with the first year of primary education. We believe that this process still needs to be studied and debated, because even though the laws and their regulations guarantee the right to education in institutions adjusted for the inclusion of six-year-olds, there is still a lot to be done, it is necessary to guarantee the permanence of the child in the educational space by improving the conditions and access to educational institutions.